The effect of learning styles on employee performance among adults working Gen Y / Hani Wahab and Fadilah Puteh - Wahab, Hani; Puteh, Fadilah (2021)
Globalization poses challenges to the millennials in terms of underemployment, mismatch skill, lack of soft skill valued, and low language fluency due to poor performance, which reflecting through inefficiency, incapability, and unsatisfactory attitude or work task among the management or other senior employees in the workplace (Lim, 2016). Thus, developing the employee’s knowledge and skills constantly helps to improve millennials' performance and enhance their positive attitude in work-related (Elqadri et al., 2015). Lim (2016) highlighted the ineffective productivity and employee’s unquantifiable ability during performing job tasks due to unutilized learning skills, and information management influence poorly towards organization development. In contrast, Reilly (2012) and Hershatter and Epstein (2010) explained the organization's effectiveness boost up and produces a great impact when workplace learning among employees is address and acknowledge properly. Moayyeri and Chaudhary et al. (2015) added that the VARK model has been used by most scholars as a classical learning theory and practical mode of assessment. Developed by Neil Fleming in 1987s, the VARK model comprises of four modes: visual, auditory, read/write, and kinesthetics where some were bimodal or trimodal or tetra modal, or even quad modal of learning styles. This study utilizes two theories which are Knowles’s Adult Learning Theory (Ismail, Abdul- Majid, & Musibau, 2017; Nelson, 2016) as it describes the best principles on the adult learning adaption based on behavior and cognitive or known as andragogy that are completely different with pedagogy or children learning. One more related theory is the Knowledge Management (KM) Theory (Peng et al., 2018; Caruso, 2017) that prioritizes the application and element of intangible resources like knowledgeable human capital which concerns closely towards the assets of knowledge in the organization process. This study aims to investigate the relationship and effect as well as to determine the preferred learning styles among adults working Gen Y.